Generational Accounting for France - Dore, Ousmane (IMF Working Papers; Working Paper, 1998)
This paper presents the first set of generational accounts prepared for France, illustrating the impact on different generations of current policy settings. It was developed using age profiles of taxes and transfers drawn from a 1990 survey and recent demographic projections. The results reported suggest that if all living generations were protected from future policy changes, current policy rules would imply a net tax burden on future generations more than 1 1\2 times as large as that on current newborn generations. If the assumption that young living generations are protected is relaxed, a large net-tax imbalance in favor of 'babyboomers' emerges.